Нове бачення механізмів сіркової вулканізації: теоретичне дослідження - Bodachivskyi, I. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2020)
Sulfur vulcanisation, of alkenes is a widely employed industrial chemical process delivering a range of organic polysulfanes as principal products. Notwithstanding their practical importance, the fundamen-tal understanding of thermally activated vulcanisation without the use of accelerants is available only in restricted sense: it is highly unselective process and there is little knowledge whether the accompa-nying reactions occur through ionic or free-radical mechanisms. Here, the work details the mechanism of the sulfur vulcanisation under non-accelerated conditions using density functional computations at B3PW91/6-311+G(3d,f) level of theory in a simulated reaction system at the temperature of sulfur polymerisation (432.15 K). The study starts from the investigation of the homolytic and heterolytic S–S bond dissociation of the octasulfur ring and its transformations into other reactive forms. It predicts that the heterolysis is a principal reaction leading to the octasulfur zwitterions, relative to the homoly-sis into diradicals, as well as that the formation of macrocyclic sulfur derivatives is more likely to take place as opposed to linear analogous products; however, it also demonstrates that disulfur diradicals might favourably form via pseudoreversible decomposition of macrocyclic sulfur into the initial eight-membered ring form. This work also analyses model reactions between sulfur and cis-2-butene via addition to double bonds or through the substitution of allyl hydrogens identifying preferred reaction pathways. Possibly, the addition products are generated from the reaction of the alkene and the oc-tasulfur through the formation of zwitterions. Alternatively, disulfur diradicals may substitute allyl hydrogens forming hydrodisulfanes that further convert into polysulfanes by the addition to double bonds or by the oxidation with molecular oxygen.